2018
DOI: 10.1126/sciadv.aar4297
|View full text |Cite
|
Sign up to set email alerts
|

Flavivirus serocomplex cross-reactive immunity is protective by activating heterologous memory CD4 T cells

Abstract: Sequential exposures to flaviviruses sharing CD4 epitopes promote protection during subsequent heterologous infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
88
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 67 publications
8
88
0
Order By: Relevance
“…Peptides derived from the aforementioned sequences were used to prime antigen presenting cells, which were subsequently used to stimulate splenocytes of DENV immunized mice. Some of these peptides induced enrichment of T memory cells as well as IFNγ production and proliferation, confirming cross-reactivity (33).…”
Section: Flavivirusessupporting
confidence: 61%
See 1 more Smart Citation
“…Peptides derived from the aforementioned sequences were used to prime antigen presenting cells, which were subsequently used to stimulate splenocytes of DENV immunized mice. Some of these peptides induced enrichment of T memory cells as well as IFNγ production and proliferation, confirming cross-reactivity (33).…”
Section: Flavivirusessupporting
confidence: 61%
“…This protection was conferred by CD8 + T cells, limiting trans-placental transmission of ZIKV (32). Although cross-reactivity between DENV and ZIKV is the most prominent example, other flaviviruses, such as yellow fever virus (YFV) and Japanese encephalitis virus, also prime T cell responses toward a subsequent heterologous DENV infection in mice (33). In this context, the investigators identified homologous sequences between the flavivirus polyproteins.…”
Section: Flavivirusesmentioning
confidence: 99%
“…Enzyme-linked immunosorbent assay (ELISA)], supporting its close relationship to DENV but indicating that it falls into an independent serocomplex (11,12). First described using human sera, these flavivirus cross-reactive immune responses appear to be consistent for multiple mammalian species, including rodents and non-human primates (13)(14)(15). During the acute phase of infection and disease, flavivirus crossneutralizing antibodies can be induced, but these are usually not durable and cross-neutralization is not retained following a few months (12).…”
Section: Classification and Antigenic Relationships Among Flavivirusesmentioning
confidence: 95%
“…In this group, DENV infection stimulated a higher frequency of these cells, but remarkably, also increased highly cross-reactive IFN-γ-producing CD4 + T cells directed to DENV E, and ZIKV E/NS proteins. A study showed that cross-reactive ZIKV-primed CD4 + T cells 73 . On the other hand, we showed that naïve animals with DENV de novo response did not cross-neutralized ZIKV at all, which state that although similar, antigenic differences are sufficient to mount predominantly type-specific rather than crossreactive responses during a primary infection 50,55 .…”
Section: Higher Proportion Of Ifn-γ and Tnf-α Producing T Cells Beformentioning
confidence: 99%